A QUALITATIVE STUDY ABOUT THE RELATION BETWEEN INTRINSIC REWARDS AND ORGANIZATIONAL PERFORMANCE IN KARANG TARUNA MANADO - Christianto, Kakomore D.; Saerang, David P.E; Tulung, Maria V.J (Universitas Sam Ratulangi, 2018)
Abstract: Intrinsic rewards are very important part in an organization that sometimes has been forgotten its importance. It has such a big relation with organizational performance. But some organization or company only relaying on extrinsic rewards or salary in terms of developing and maintaining the organizational performance or employees’ performance. There are four descriptions about intrinsic rewards that has been used in this research which are, sense of meaningfulness, sense of choice, sense of competence and sense of progress. The aim of this study is to analyze the relation between intrinsic rewards and organizational performance. This research is casual types of research which uses qualitative analysis interview method to explore the relation between Intrinsic Rewards and Organizational Performance in Karang Taruna Manado. And it has been found the importance of intrinsic rewards and how big its relation with organizational performance. The organization should maintain the good performance by keeping the intrinsic rewards inside their members.Keywords : intrinsic rewards, organizational performance, intrinsic rewards in today’s work